Effectiveness of maintenance treatments for nonsmall cell lung cancer - Eadens MJ (Dove Medical Press, 2011)
Matthew J Eadens, Steven I Robinson, Katharine AR PriceDivision of Medical Oncology, Mayo Clinic, Rochester, MN, USAAbstract: Maintenance therapy for advanced nonsmall cell lung cancer has shown some clinical benefit for patients by improving progression-free survival and, to a lesser extent, overall survival. Two main strategies exist for maintenance therapy, ie, continuation and switch maintenance. Continuation maintenance involves the continued use of one of the induction drugs beyond 4–6 cycles of initial treatment. Switch maintenance utilizes a third agent initiated after first-line chemotherapy. Both cytotoxic agents and targeted agents have been studied. Switch maintenance therapy with pemetrexed in nonsquamous tumors and erlotinib appear to show the most clear clinical benefit. Continuation maintenance with bevacizumab has shown improvement in progression-free survival. Data concerning the role of cetuximab for maintenance is conflicting. Toxicity, quality of life, and cost are important confounding issues that need to be considered. Several ongoing Phase III trials are investigating strategies to improve on the current agents as well as testing promising new therapies.Keywords: lung cancer, chemotherapy, maintenance therapy, targeted therapy